Diagnostic Utility of Common Brain MRI Technique in Pediatric Epilepsy: A Cross-Sectional Study: MRI Findings in Pediatric Epilepsy - Babaei, Meisam; Tavakoli, Maryam; Heidari, Faeze (Iranian Journal of Child Neurology, 2026)
Objectives: Pediatric epilepsy is a neurological condition that could be associated with structural brain abnormalities. Although the common magnetic resonance imaging (MRI) technique is a standard tool for detecting these abnormalities, its diagnostic utility remains unclear compared to advanced neuroimaging techniques. This study aimed to evaluate the effectiveness of the common brain MRI technique in identifying structural lesions in pediatric epilepsy. Materials & Methods: In this cross-sectional investigation, 337 patients with pediatric epilepsy underwent a common brain MRI. The scans were examined for abnormal lesions and assessed for their connections with neurological characteristics. Chi-square tests were used in statistical analysis to detect essential connections. Results: Brain MRI scans revealed abnormalities in 20.7% of patients. These abnormalities included white matter lesions (72%), gray matter lesions (22%), hippocampal lesions (12.8%), ventricular lesions (7%), and vascular lesions (2.8%). A significant relationship was found between abnormal neurological exam results and brain MRI findings (p < 0.001). Conclusion: While standard brain MRI can help identify structural abnormalities in pediatric epilepsy, it is not the most sensitive method, particularly compared to advanced neuroimaging techniques. Higher-resolution imaging and advanced modalities such as diffusion tensor imaging (DTI) and functional MRI (fMRI) may enhance diagnostic accuracy and improve outcomes in pediatric epilepsy management